Jordanes in the Constantinople milieu of the mid-6th century. Preliminary remarks - Salamon, Maciej (Balcanica Posnaniensia. Acta et studia, 1990)
The article concerns the environment in which Jordanes operated in the mid-6th century. The research problem includes determining the place of his activity (Constantinople or Italy) and the influence of his surroundings on his work. The aim of the work is to analyze the political and cultural context of the author. The author applies historiographical and source analysis. The most important results indicate that it is more probable that Jordanes was connected with Constantinople rather than Italy. The author analyzes the intellectual environment of the capital, including the role of monasteries (e.g., the Akoimetoi), access to literature, and connections with political elites. He also points to possible ideological links between Jordanes and this environment. The conclusion is that the Constantinopolitan context had a significant influence on his work and his interpretation of the history of the Goths.